Discontinuation of Tenofovir Disoproxil Fumarate for Presumed Renal Adverse Events in Treatment-Naïve HIV-1 Patients: Meta-analysis of Randomized Clinical Studies. Issue 6 (November 2014) - Winston, Jonathan; Chonchol, Michel; Gallant, Joel; Durr, Jacques; Canada, Robert B.; Liu, Hui; Martin, Patty; Patel, Kiran; Hindman, Jason; Piontkowsky, David
Abstract : Background: Safety and efficacy of tenofovir disoproxil fumarate (TDF) as a component of antiretroviral therapy (ART) have been demonstrated in clinical trials. TDF nephrotoxicity has been reported in both HIV-infected and noninfected patients. This meta-analysis explored the frequency of discontinuation attributed to renal adverse events (AEs) in randomized, controlled clinical studies that used TDF-containing regimens for ART-naïve, HIV-infected patients.Methods : A literature search of 4 electronic databases through October 31, 2013 was utilized. RCTs included were limited to randomized, prospective, comparative design in ART treatment-naïve adults with HIV-1 infections receiving ART. Studies included trials containing TDF treatment regimens, with or without a non-TDF control group. Study design, follow-up, size of study population, treatment group, patient demographics, number of patients exposed to TDF or non-TDF control, baseline characteristics, investigator-defined criteria for renal AEs, and number of discontinuations due to a presumed renal AEs were extracted.Results: Twenty-one clinical studies met the selection criteria. Treatment duration ranged from 48 to 288 weeks. Renal AEs led to study drug discontinuation in 44 of 10, 129 patients exposed to TDF (0.43%; 95% CI, 0.32%-0.58%) and 2 of 2, 013 patients exposed to non-TDF-containing regimens (0.10%; 95% CI, 0.01%-0.36%). In 5 randomized, controlled studies that included a non-TDF comparator, the estimated risk difference between the treatment groups (TDF vs non-TDF) was 0.50% (95% CI, 0.13%-0.86%; P = .007).Conclusions: In clinical studies using TDF-containing regimens, the rate of discontinuations due to renal AEs was low, but was slightly higher than in studies using non-TDF comparators.